My first book of baby signs : 40 essential signs to learn and practice - Rebelo, Lane (Rockridge Press, 2021)
Learn sign language alongside your baby with an adorable storybook designed to encourage you to learn new words and signs as you read together. Interactive learning that includes 40 real ASL signs.